1984
DOI: 10.1152/ajpcell.1984.247.3.c260
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial properties of human colonic carcinoma cell line Caco-2: electrical parameters

Abstract: Human colonic carcinoma Caco-2 cells grown in vitro undergo epithelial differentiation. Electrical measurements showed that they form resistant monolayers of polarized cells. On millipore filters, transepithelial electrical resistance (154 +/- 6.5 omega X cm2) was accompanied by a small potential difference (0.29 +/- 0.02 mV, serosal side positive) and by short-circuit current (1.9 +/- 0.14 microA X cm-2), both of which were ouabain sensitive. Micropuncture of domes formed on plastic supports under standard cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
0
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(215 citation statements)
references
References 24 publications
11
202
0
2
Order By: Relevance
“…After hAIP cells completely covered the bottom of culture dishes as a monolayer sheet, we found cells that formed dome-like structures (Figures 6d and e). These dome-like structures, derived from hAIP cells, resembled those from Caco-2 cells, a well-known cell line obtained from human colon carcinoma, 32 suggesting that hAIP cells differentiated into enterocytes capable of transporting ions and water from apical to basolateral membrane. The hAIP cell cultures included cells expressing the enteroendocrine cell markers serotonin, chromogranin A, GIP, and synaptophysin; the Paneth cell marker lysozyme; and mucin-producing PASpositive cells (Figure 7a).…”
Section: Culture Of Intestinal Epithelial Cells Isolated From Adult Hmentioning
confidence: 81%
See 1 more Smart Citation
“…After hAIP cells completely covered the bottom of culture dishes as a monolayer sheet, we found cells that formed dome-like structures (Figures 6d and e). These dome-like structures, derived from hAIP cells, resembled those from Caco-2 cells, a well-known cell line obtained from human colon carcinoma, 32 suggesting that hAIP cells differentiated into enterocytes capable of transporting ions and water from apical to basolateral membrane. The hAIP cell cultures included cells expressing the enteroendocrine cell markers serotonin, chromogranin A, GIP, and synaptophysin; the Paneth cell marker lysozyme; and mucin-producing PASpositive cells (Figure 7a).…”
Section: Culture Of Intestinal Epithelial Cells Isolated From Adult Hmentioning
confidence: 81%
“…The flat morphology of mouse FIP/AIP cells and hAIP cells differs from that of Caco-2 and other colon cancer cell lines, which can form polarized monolayers in culture. 20,32 Therefore, the morphological maturation of cultured normal intestinal epithelial cells will require further improvements in culture conditions, including a supply of an ideal set of ECM components and additional humoral factors. Normal intestinal epithelial cells that can reproduce in culture the gene expression pattern and well-defined morphological features of epithelial cells will be useful in developing therapeutic approaches, including repair of intestinal mucosa, and in screening the pharmacological effects of new compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of HNF-1␣ in the coculture system does not improve differentiation, an observation that correlates well with the absence of morphological defect in the intestinal epithelium of HNF-1␣ knockout mice (4). However, forced expression of HNF-4␣ leads to complete polarization and features normally associated with apical-to-basal transport (15) (Fig. 9B).…”
Section: Discussionmentioning
confidence: 95%
“…Total RNA was isolated from cultured cells and subjected to a DNase treatment according to the manufacturer's instructions (Totally RNA kit). Reverse transcriptions were carried out at 42°C for 1 h in the presence of 2 g RNA, 40 mU of polyoligo(dT) [12][13][14][15][16][17][18], and 40 U of Reverse Transcriptase (Roche Diagnostics). Semiquantitative PCR was performed in a total volume of 20 l in the presence of 1 l of RT reaction, 0.6 U of Taq DNA polymerase (New England Biolabs), 0.2 mM dNTPs, and 30 ng of each specific primer.…”
Section: Methodsmentioning
confidence: 99%
“…Discussion Recently two human colonic cell lines, other than HCA-7, have been used to examine epithelial ion transport, but kinin effects are not reported; they are T84 and Caco-2 (Dharmsathaphorn et al, 1984;Grasset et al, 1984). Both groups showed that their monolayers had small transepithelial potentials and low resistances comparable to those in HCA-7 monolayers.…”
Section: Introdutionmentioning
confidence: 95%